Public social trust and acceptance of task shifting to hospital paramedics as a response to physician shortages - Satoshi Kondo; Shuhei Ichikawa; Shuji Hashimoto; Masashi Izumiya; Masato Eto (PLOS One, 2026)
Background Physician shortage is a crucial global issue. Some countries have introduced task shifting to expand paramedics’ roles. This expansion requires citizens’ social trust in paramedics in general. During medical emergencies, citizens must allow treatment by paramedics, with whom they often have no prior relationship. Although social trust is vital in medical emergencies, its level among hospital paramedics is unclear. This study aimed to evaluate citizens’ social trust in hospital paramedics and their acceptance of the paramedics’ medical practices, as well as the impact of educational outreach regarding hospital paramedics. Methods In this within-participant pre–post assessment, citizens completed a web-based questionnaire distributed online to assess social trust in hospital paramedics before and after receiving information about hospital paramedics. Social trust was assessed using a validated questionnaire, and acceptance of paramedic medical practices was evaluated using a five-point Likert scale. Descriptive analyses were performed to assess social trust and acceptance of paramedic medical practices. The impact of educational outreach was evaluated using mean differences and corresponding confidence intervals. Results A total of 630 participants were included. Citizens’ social trust in hospital paramedics and their acceptance of paramedic medical practices were high. After educational outreach regarding hospital paramedics, acceptance of their practices showed a statistically significant but modest improvement, whereas social trust did not show a statistically significant change. Conclusions Society may already accept hospital paramedics’ activities because social trust in ordinary paramedics has already been established. Task shifting to allied healthcare professionals to address physician shortages may require credible certification and education systems to gain high social trust and acceptance of hospital paramedics.